Everolimus dosing recommendations for tuberous sclerosis complex–associated refractory seizures. (4th May 2018) - Franz, David N.; Lawson, John A.; Yapici, Zuhal; Brandt, Christian; Kohrman, Michael H.; Wong, Michael; Milh, Mathieu; Wiemer‐Kruel, Adelheid; Voi, Maurizio; Coello, Neva; Cheung, Wing; Grosch, Kai; et al.
Summary: Objective: The present analysis examined the exposure‐response relationship by means of the predose everolimus concentration ( C min ) and the seizure response in patients with tuberous sclerosis complex–associated seizures in the EXIST‐3 study. Recommendations have been made for the target C min range of everolimus for therapeutic drug monitoring (TDM) and the doses necessary to achieve this target C min . Methods: A model‐based approach was used to predict patients' daily C min . Time‐normalized C min (TN‐ C min ) was calculated as the average predicted C min in a time interval. TN‐ C min was used to link exposure to efficacy and safety end points via model‐based approaches. A conditional logistic regression stratified by age subgroup was used to estimate the probability of response in relation to exposure. A multiplicative linear regression model was used to estimate the exposure‐response relationship for seizure frequency (SF). An extended Cox regression model was used to link exposure to the time to first adverse event. Results: There was a strong, consistent, and highly significant relationship between everolimus exposure and efficacy, measured by TN‐ C min and SF, regardless of patient's age and concomitant use of cytochrome P450 3A4 (CYP3A4) inhibitors/inducers. Results of an extended Cox regression analyses indicated that twofold increases in TN‐ C min were not associated with statistically significant increases in the risk of stomatitis or infections. Significance: The recommended TDM is to target everolimus C min within a range of 5‐7 ng/mL initially and 5‐15 ng/mL in the event of an inadequate clinical response, and safety is consistent with previous reports. Starting doses depend on age and the concomitant use of CYP3A4/P‐glycoprotein inducers/inhibitors.